SECONDARY ETIOLOGICAL FACTORS IN THE DEVELOPMENT OF PERI-IMPLANTITIS - Elitsa Sabeva (Peytchinski Publishing, 2021)
Purpose: The aim of this review was to investigate the potential impact of secondary etiological factors on the development of peri-implant infections. Results: During the review process we found sufficient evidence to define the following factors as secondary etiological factors for the development of peri-implantitis: a history of periodontitis; implant surface characteristics; suprastructure characteristics; cemented restorations; implant-abutment connection; smoking; diabetes and peri-implant mucosa characteristics. Conclusion: To reduce the risk of peri-implantitis, the following recommendations should be considered: (1) in partially edentulous patients, implant treatment should start after elimination of the periodontal infection and after the establishment of a stable periodontal status; (2) implants should be placed in areas where there is a minimum of 2 mm of keratinized mucosa; (3) an internal implant-abutment connection and screw-retained suprastructures are preferred; (4) suprastructures should be planned carefully to facilitate good oral hygiene; and (5) smoking cessation should be promoted and (6) only patients with controlled diabetes should undergo implant placement.